DIFFERENCES IN DIETARY PATTERNS AND NUTRITIONAL STATUS BETWEEN UNIVERSITY STUDENTS LIVING IN DORMITORIES AND THOSE LIVING WITH THEIR PARENTS: A COMPARATIVE CROSS-SECTIONAL STUDY - Maya Arsyad; Tri Setiawati Maulana (Jurnal Ilmiah dr. Aloei Saboe, 2025)
University students often experience lifestyle changes that influence their dietary behaviors and nutritional status, particularly when they transition from living with their parents to living independently in dormitories. This study aimed to analyze differences in dietary patterns and nutritional status between students living in dormitories and those living with their parents. A quantitative comparative study with a cross-sectional design was conducted among 60 undergraduate students, consisting of 30 dormitory residents and 30 students living with their parents. Participants were selected using purposive sampling. Data were collected using a structured questionnaire assessing meal frequency, breakfast habits, fruit and vegetable consumption, and fast-food consumption, while nutritional status was determined using Body Mass Index (BMI). Descriptive statistics were used to summarize respondents' characteristics, and differences between the two groups were analyzed using the Pearson Chi-square test with a significance level of 0.05. The findings showed that students living in dormitories were more likely to have irregular meal frequency, skip breakfast, and consume fast food more frequently than students living with their parents. In addition, a higher proportion of overweight and obesity was observed among dormitory students, whereas normal nutritional status was more prevalent among students residing with their parents. Statistical analysis indicated significant differences in dietary patterns and nutritional status between the two residence groups (p < 0.05). These findings suggest that living arrangement plays an important role in shaping dietary behaviors and nutritional outcomes among university students. Universities should strengthen nutrition education and promote healthier food environments, particularly for students living independently.